Design of a multi-cusp ion source for proton therapy - 吴小兵 黄涛 欧阳华甫 张华顺 巩克云 (Chinese physics C, 2010)
The permanent magnets of the discharge chamber in a multi-cusp proton source are studied and designed. The three electrode extraction system is adopted and simulated. A method to extract different amounts of current while keeping the beam emittance unchanged is proposed.